TANTANGAN DAN PELUANG IMPLEMENTASI PAJAK PENGHASILAN PROGRESIF DI INDONESIA: Indonesia - Awaliya Awaliya; Vivi Rahmadani Siregar; Fidya Purnama; Dini Vientiany (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Progressive Income Tax (PIT) is a tax system where tax rates rise proportionally with income. This ensures a fairer and more equitable distribution of the tax burden, while also encouraging higher contributions from those with greater financial means.Indonesia has a long history with PIT, but its implementation faces some hurdles. One key challenge is the lack of comprehensive and accurate data on taxpayer income. This makes it difficult to establish the appropriate tax bracket for each individual. Another obstacle lies in the prevalence of tax avoidance strategies. Wealthier taxpayers often exploit loopholes to minimize their tax obligations. Furthermore, public education regarding PIT remains inadequate. Many taxpayers lack a clear understanding of the system and its benefits for society.Despite these challenges, opportunities exist to strengthen the implementation of PIT in Indonesia. By leveraging information technology, the accuracy and completeness of taxpayer data can be significantly improved. Additionally, stricter enforcement of tax laws can deter non-compliant taxpayers. Finally, increased public education and outreach programs can raise awareness about PIT and its role in a just and equitable society.By addressing these challenges and capitalizing on existing opportunities, PIT can be a powerful tool for achieving fairness and equity in tax collection, as well as securing a larger contribution from high-income earners to the national treasury.